Protective roles of adiponectin in obesity-related fatty liver diseases: mechanisms and therapeutic implications - Wang,Yu (2009)
Adiponectin is an insulin-sensitizing adipokine possessing multiple beneficial effects on obesity-related medical complications. This adipokine is secreted from adipocytes into the circulation as three oligomeric isoforms, including trimer, hexamer and the high molecular weight (HMW) oligomeric complex. Each oligomeric isoform of adiponectin possesses distinct biological properties and activates different signaling pathways in various target tissues. The hepato-protective activities have been demonstrated by many clinical and experimental studies. The decreased level of serum adiponectin represents an independent risk factor for nonalcoholic fatty liver disease (NAFLD) and liver dysfunctions in humans. In animals, elevation of circulating adiponectin by either pharmacological or genetic approaches leads to a significant alleviation of hepatomegaly, steatosis and necro-inflammation associated with various liver diseases. In adiponectin knockout mice, there is a pre-existing condition of hepatic steatosis and mitochondria dysfunction, which might contribute to the increased vulnerabilities of these mice to the secondary liver injuries induced by obesity and other conditions. This review aims to summarize recent advances on delination of the structural, molecular and cellular mechanisms underlying the hepato-protective properties of adiponectin.